(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the issues of forming an individual’s information culture in the information society. In particular, the role of parents in developing the skills of correctly perceiving, selecting, analyzing and effectively using information in the minds of children and adolescents is scientifically highlighted. Also, the pedagogical and psychological aspects of the correct organization of the information environment in the family, the mechanisms of control and guidance in the process of children’s use of the Internet and mass media are considered. According to the results of the study, the creation of a healthy information environment in the family is an important factor in the formation of independent thinking, critical analysis and conscious perception of information in children.